Drivers behind the changes in European banks' capital ratios: a descriptive analysis - Wouter Heynderickx; Jessica Cariboni; Marco Petracco Giudici (European Commission, Joint Research Centre (JRC), 2016)
After the financial crisis financial regulators increased banks' capital adequacy ratios (CET1/RWA) requirements in order to make the financial system more resilient. The new capital requirements could be achieved through different channels, some of which might affect bank's ability to finance the real economy. We perform a decomposition of the changes in capital adequacy ratios into seven factors to check whether banks adjusted their capital ratio by increasing equity, by reducing loans or securities, or by reducing the riskiness of their assets' portfolio. We employ consolidated balance sheet data of 257 European banking groups including M&A operations and state aid and covering the 2005-2014 period, and find that the main driver alters over time. Our decomposition shows that during the financial crisis the augmentation was mainly driven by new share issuances and government recapitalizations, while during the sovereign crisis a reduction in the RWA-density (RWA/TA) is found. In the post crisis period, we observe a large income effect and a reduction in total assets. Decompositions are also performed at country and major banking group level, showing high heterogeneity in responses to achieve the new requirements.
Keywords: G21; G28; 330; banks; capital ratio; decomposition; regulation; Basel III